Impact of lunch provision on the nutritional and health status of garment workers in Cambodia - Makurat, Jan; Justus Liebig University Giessen (My University, 2018)
Although concerns about the nutritional and health status of Cambodian garment workers do exist, data are still sparse. The establishment of staff canteens in garment factories serving free lunch has been proposed as a suitable intervention to improve nutrition and health of workers. However, trials that verify this hypothesis are missing and information is lacking on exemplary meals, their nutritive value, and their costs.The objectives of the present thesis are: 1) to examine the nutritional, hemoglobin (Hb), and micronutrient status of female workers employed by a garment factory in Phnom Penh, Cambodia; 2) to assess the nutritive value of low-price model lunch sets provided to garment workers within the Lunch Provision in Garment Factories study (LUPROGAR); 3) to compare food intake between garment workers with and without access to LUPROGARs model lunch provision; and 4) to determine the impact of LUPROGARs model lunch provision on anthropometry, Hb, and micronutrient status of female Cambodian garment workers.The LUPROGAR study was an exploratory randomized controlled trial implemented at a garment factory in Phnom Penh, Cambodia. Female workers (nulliparous, non-pregnant) were recruited and randomly allocated into an intervention arm (six-month free model lunch provision through a newly established canteen during workdays) and a control arm. Exemplary low-price lunch sets (~700 kcal on average, biweekly menu) included diverse local dishes prepared by an established local caterer. At baseline and after five months of lunch provision, anthropometric measurements (body mass index (BMI), weight, triceps skinfold thickness (TSF), and mid-upper arm circumference (MUAMC)) were performed and blood samples were taken to obtain results on Hb, serum ferritin (FER) and soluble transferrin receptor (sTfR), serum retinol binding protein (RBP), serum folate, and serum vitamin B12 (VitB12) concentrations. Dietary intake on workdays was assessed at baseline and at two follow-up interviews during the lunch provision period (first follow-up at two and a half months and second follow-up at five months) using the Food and Agricultural Organization (FAO) guideline on recording individual dietary diversity. At the canteen, dish samples were collected repeatedly to examine mean serving sizes of individual ingredients. Food composition tables and NutriSurvey software were used to assess mean amounts and contributions to recommended dietary allowances (RDAs) or adequate intake of energy, macronutrients, dietary fiber, vitamin C (VitC), iron, vitamin A (VitA), folate, and VitB12.
Keywords: ddc:630